Osteomyelitis of the Foot among Patients Presenting with Diabetic Foot Ulcers: A Retrospective Analysis (Journal of Pakistan Orthopaedic Association, 2017)
Objective: To assess the prevalence of osteomyelitis of the foot, diagnostic accuracy of investigations and outcome of conservative treatment in patients presenting with non-healing diabetic foot ulcers at the outpatient department of Liaquat University Hospital.Methods: Retrospective data of two hundred diabetic patients (chosen via consecutive sampling) presenting with non-healing diabetic foot ulcers at the outpatient department of the Liaquat University Hospital from July 2015 to June 2016 was evaluated. All patients (as per standard routine protocol) have went under physical examination, plain x-ray and complete blood count after taking written informed consent. The results were analyzed using SPSS v. 19.0.Results: Among the 200 patients, presenting with non-healing diabetic foot ulcers, evaluated and managed in the outpatient department, 120 (60%) patients were evaluated positive for osteomyelitis on the basis of positive clinical presentation i.e., laboratory data and radiographic imaging. 30 (15%) of the diagnosed patients later met with grim fate of amputation while the rest (i.e., 50, 25%) yielded positive outcomes. Among the measure employed to assess the patients, all worked in tandem. However the accuracy rates varied.Conclusions: We conclude that conservative therapy more often than not, yielded positive results. It is recommend that patients at risk should be evaluated for osteomyelitis in the outpatient setting so that the disease may be diagnosed at early stage and thus helping to bring down the amputation rates.